IJAR 2019
DOI: 10.21474/ijar01/8977
|View full text |Cite
|
Sign up to set email alerts
|

Study of Serum Calcium, Magnesium and Uric Acid in Preeclampsia and Its Comparison With Normal Pregnancy.

Abstract: Preeclampsia is one of the common causes of maternal and foetal morbidities and mortalities. Its incidence is 4-8% of pregnancies. Preeclampsia is defined as the triad of hypertension, proteinuria and oedema occurring after 20 weeks gestation in previously normotensive women. Interestingly, variable serum calcium, magnesium and uric acid levels are found in preeclampsia. The data was collected from normal pregnant women and pre-eclamptic women who were admitted in the Department of Obstetrics and Gynaecology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The serum magnesium in pre-eclamptic women was also significantly lower in comparison to healthy pregnant women, which is consistent with the findings of a number of recent studies. 2,3,10,13,14,[16][17][18][19][20]24,28 An increase in renal clearance during pregnancy, poor dietary intake, consumption of minerals by growing fetal skeletal systems, and haemodilution, all contribute to hypomagnesemia. However, several studies reported no association of magnesium with preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The serum magnesium in pre-eclamptic women was also significantly lower in comparison to healthy pregnant women, which is consistent with the findings of a number of recent studies. 2,3,10,13,14,[16][17][18][19][20]24,28 An increase in renal clearance during pregnancy, poor dietary intake, consumption of minerals by growing fetal skeletal systems, and haemodilution, all contribute to hypomagnesemia. However, several studies reported no association of magnesium with preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is compatible with the previous studies. 3,24,31,32,33 Two studies 34,35 however did not find any significant association between serum uric acid and preeclampsia. In their study, all subjects were primigravida with singleton pregnancy and were recruited before their 20 th week of gestation.…”
Section: Group Biochemical Parametersmentioning
confidence: 96%